The Strategic Role of the Defense Industry in Answering the Needs of KRI Capability C4ISR to Achieve Maritime Security in Indonesian National Jurisdictions - Novie Adolof Dolonseda (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2022)
The increasingly growing and complex maritime security threats identified by the emergence of the Coronavirus outbreak needed to spread quickly. This virus threat can mean Hybrid Warfare and a proxy where this type of threat can be exploited or used by parties who intend to invest their interests in Indonesia. This threat must be the concern of all countries, and cooperation in the sea between countries required in dealing with it. The Indonesian Navy sees the importance of increasing capabilities in using C4ISR technology (Command, Control, Computer, Communication, Intelligence, Surveillance, And Recognition) and how to combine it into one unit that can operate in an integrated manner within the Indonesian Navy. The framework of maritime defense and security of the Unitary State of the Republic of Indonesia. Furthermore, the cooperation of the Navy with all maritime stakeholders is also urgently needed to build pleasing cooperation to realize Maritime Domain Awareness (MDA) in the National area. The importance of Indonesia as a regional maritime security barometer, namely; as a measure of the independence of Indonesia's ability to face maritime security threats, measurable patterns, methods, and technology of Indonesian maritime security forces in dealing with threats, as well as predicting trends in maritime security threats that occur. The Indonesian Navy, as the main component of national defense, is required to carry out capacity building in maritime defense and security so that the defense industry's role is needed to provide and realize C4ISR-based force development.